Synthesis of a Cellulose/PVA Adsorbent Composite from Pineapple Leaves Waste (Ananas Comosus) for the Degradation of Methylene Blue in Aqueous Solution - Mayangsari, Novi Eka; Ramadani, Tarikh Azis; Astuti, Ulvi Pri (Indonesian Journal of Chemical Analysis (IJCA), 2025)
Methylene blue is disastrous for the environment due to their high toxicity. This needs to be mitigated to ensure that the effects can be reduced. Pineapple peel waste (Ananas comosus) can be valorized as cellulose adsorbent and cellulose/PVA adsorbent is a potential solution to minimize the impact of these contaminants. The objective of this research is to investigate the performance of the cellulose/PVA composite in the methylene blue adsorption process and to evaluate its performance with a cellulose adsorbent. The adsorption process results showed that the percentage of MB removal reached 94.03% on the cellulose/PVA adsorbent with 9% NaOH delignification for 90 minutes. After adding PVA, there was a significant increase in the removal of methylene blue in the adsorbent was recorded. The results indicate that cellulose and cellulose/PVA composites are more effective adsorbents than cellulose alone for removing methylene blue.